2020
DOI: 10.1111/opn.12332
|View full text |Cite
|
Sign up to set email alerts
|

Promoting dietary awareness: Home‐dwelling older adults’ perspectives on using a nutrition application

Abstract: This is an open access article under the terms of the Creative Commons Attribution-NonCommercial License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited and is not used for commercial purposes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 35 publications
0
13
0
Order By: Relevance
“…For example, studies have demonstrated that recording fruit and vegetable consumption in an app can be a powerful tool to increase awareness of low consumption levels, leading to increased consumption (Mummah et al, 2017; Steinert, Haesner, Tetley, & Steinhagen‐Thiessen, 2016). This article as well as our previous work suggests that interest in and awareness of an age‐friendly diet increased among older adults as they used Appetitus to self‐monitor their diets—many implemented dietary changes (Aure, Kluge, & Moen, 2020). It is still unclear how long and how often it is necessary to engage in dietary self‐monitoring to foster long‐standing eating habits that are beneficial for health (Michie, Yardley, West, Patrick, & Greaves, 2017).…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…For example, studies have demonstrated that recording fruit and vegetable consumption in an app can be a powerful tool to increase awareness of low consumption levels, leading to increased consumption (Mummah et al, 2017; Steinert, Haesner, Tetley, & Steinhagen‐Thiessen, 2016). This article as well as our previous work suggests that interest in and awareness of an age‐friendly diet increased among older adults as they used Appetitus to self‐monitor their diets—many implemented dietary changes (Aure, Kluge, & Moen, 2020). It is still unclear how long and how often it is necessary to engage in dietary self‐monitoring to foster long‐standing eating habits that are beneficial for health (Michie, Yardley, West, Patrick, & Greaves, 2017).…”
Section: Discussionmentioning
confidence: 75%
“…Having knowledge and skills in using tablet technology was not crucial to the older adults' ability to use Appetitus or whether they used it regularly. This indicates that the app was user friendly and that the participants received sufficient training and support from the healthcare professionals during the trial (Aure et al, 2020;Wildenbos et al, 2018). The app's interface is the outcome of an extensive co-design process accompanied by iterative evaluations and a pilot study with potential users, ensuring that the final version of the interface was suitable for older adults, including those without prior technology use (Fuglerud et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Less frequently considered nutrition topics included status, weight and body composition, and ADL. Several studies used technology to improve nutrition status of malnourished or at nutritional risk (e.g., Aure et al, 2020). Three studies examined how technology can promote weight loss (e.g., Batsis et al, 2019).…”
Section: Nutrition Focus Characterizationmentioning
confidence: 99%
“…Software applications: Most studies extracted utilized software applications, specifically to "assess, track and monitor" older adults' health outcomes, including dietary intake (n = 31 [3,23,40,52,54,56,[58][59][60][61][62][63][64][65]67,71,[73][74][75][76][77][78][79][80][81][82][83][84][85]87,89]). Thirteen applications served to help provide food options, recommendations, remind older adults to eat or drink, or provide nutrition education [23,40,52,54,56,58,60,61,67,75,77,83,85]. Nine studies used a software application to track and analyze diet [3,59,62,64...…”
Section: Technology Characterizationmentioning
confidence: 99%
“…Software applications were accessed using a tablet computer (n = 21 studies, [3,23,40,54,55,[58][59][60]64,67,[73][74][75]77,[79][80][81][82][83][84][85]87]) or mobile/smartphone devices (n = 7 studies [61,64,65,76,80,81,89]). Nine extracted studies that utilized software applications also incorporated internet access, where the end users needed the internet to connect to digital healthcare resources or providers [6,23,54,58,64,67,78,84,89]. Three studies using software applications utilized webcam technologies [3,81,82].…”
Section: Technology Characterizationmentioning
confidence: 99%